Enamel and dentin in Enamel renal syndrome: A confocal Raman microscopy view - Desoutter, Alban; Cases, Olivier; Collart Dutilleul, Pierre Yves; Simancas Escorcia, Victor; Cannaya, Vidjea; Cuisinier, Frédéric; Kozyraki, Renata (Frontiers in Physiology, 2022)
Enamel Renal Syndrome (ERS) is a rare genetic disorder caused by biallelic mutations in Family with sequence similarity 20A (FAM20A) gene encoding the secretory pathway pseudokinase FAM20A. ERS is characterized by hypoplastic amelogenesis imperfecta (AI), impaired tooth eruption, intra-pulpal calcifications, gingival fibromatosis and nephrocalcinosis of various severity. Previous studies showed that the hypoplastic enamel was also hypomineralized but its chemical composition has not been extensively studied. Furthermore it is currently unclear whether dentinal defects are associated with AI in ERS patients. The objective of the study was to provide a structural and chemical analysis of enamel, dentin and dentin enamel junction (DEJ) in ERS patients carrying four, previously reported, distinct mutations in FAM20A. Chemical cartography obtained with Raman microscopy showed that compared to control samples, ERS enamel composition was severely altered and reminiscent of cement. Chemical composition of peripulpal dentin was also affected and usual gradient of phosphate intensity, shown in DEJ profile, was absent in ERS samples. DEJ and dentinal anomalies were further confirmed by scanning electron microscopy analysis. In conclusion, our study shows that enamel formation is severely compromised in ERS patients and provides evidence that dentinal defects are an additional feature of the ERS dental phenotype.